Internal Customer Service Quality Based on the SERVQUAL Model and Its Relationship with Job Satisfaction in a Heavy Freight Transportation Company in Metropolitan Lima, 2021 - Rodríguez Carrasco, Renzo José (2023)
The main objective of this research study is to determine the relationship between service quality and job satisfaction using the SERVQUAL model. Likewise, it seeks to determine the relationship between dimensions reliability, responsiveness, security, empathy, and tangible elements, and the variable job satisfaction. A methodology based on a mixed quantitative-qualitative approach was used, the level is descriptive-correlational, and the design is non-experimental and cross-sectional. The population consisted of 98 heavy truck drivers. Data were obtained through Likert-type scale surveys. The methods of analysis used were descriptive and correlational. Results indicate that the variables service quality and job satisfaction correlate positively and highly (0.783); therefore, it is concluded that internal customer service quality and all its dimensions are related to job satisfaction.